STUDI IDENTIFIKASI KUALITAS AIR DAN JENIS IKAN AIR TAWAR DI SUMBER AIR PANAS DESA NYELANDING KABUPATEN BANGKA SELATAN SEBAGAI DASAR PENGELOLAAN POTENSI KAWASAN AIR PANAS UNTUK KEGIATAN PERIKANAN DAN WISATA - M. Rizza Muftiadi; Wahyu adi; Andi Gustomi; Arthur M Farhaby (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2019)
Hot springs in Nyelanding Village, South Bangka Regency, have the potential of geothermal resources that can be used as a potential energy source, moreover found several types of freshwater fish that utilize these hot springs as their natural habitat. The objectives of this study are to identify the water quality and diversity of freshwater fish species in the hot spring area of Nyelanding Village, South Bangka Regency; analyze the feasibility of water quality for fisheries and tourism activities; and analyzing fish growth patterns found at these locations. The results showed that there were two types of fish found in the hot springs of Nyelanding Village, which were Gabus Fish (Channa striata) and Sepat Fish (Trichogaster trichopterus). There are 6 hot water quality parameters Village Nyelanding included in standard class II PP 82 of 2001 include pH, COD, TSS, TDS, Nitrate and Total fospat, two parameters are not required (depth and ammonia), one parameter (temperature ) not in normal natural waters. The growth pattern of Gabus Fish in the hot water of Nyelanding Village is negative allometric with a growth coefficient of 2.076. In general, based on the analysis of water quality parameters, the Nyelanding Village hot water is suitable for biota life as well as aquaculture activities and tourist areas. For aquaculture, the recommended type of fish is eurythermal. However, their habit of draining the hot water pool Village Nyelanding made towards development of the area is less recommended for fishing activity, but preferably as a tourist area.